Efektivitas Konseling Kelompok dalam Mengatasi Rasa Cemas pada Remaja dengan Gangguan Kecemasan - Adit Shaprizal; Desty Endrawati Subroto; Elsa Kemalia Putri; Intan Rahma; Sintya Nurmala Sari; Encih Nuraeni (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Anxiety disorders in teenagers are a serious issue that can impact various aspects of their lives, such as social interactions, academic achievement, and emotional well-being. To address these challenges, group counseling has proven to be an effective approach. In group counseling, teenagers can share their experiences with others facing similar issues, creating a supportive and understanding environment. Techniques like open discussions help them identify the causes of their anxiety more effectively, while role-playing allows them to practice new ways of dealing with anxiety-inducing situations. Relaxation exercises also assist them in developing skills to manage anxiety effectively in their daily lives. Literature studies indicate that group counseling not only reduces anxiety levels in teenagers but also enhances their social skills, self-confidence, and emotional resilience. With support from family, schools, and the community, group counseling can become a sustainable strategy in promoting teenagers' mental well-being. Therefore, it is important to consider that there is no one-size-fits-all approach for all teenagers. However, group counseling provides a safe and structured platform for teenagers to learn from each other, strengthen their coping skills, and make progress in overcoming their anxiety. With this approach, it is hoped that teenagers can build a strong foundation for their ongoing mental health.